Implementasi Konsep Galeri pada Interior Wedding Centre di Surabaya - Deviana Christyawan; Laksmi Kusuma Wardani; Jean Francois Poillot (Intra, 2017)
Marriage needs to be prepared carefully because it only happens once in a lifetime. Many wedding needs that have to be prepared but usually the bride and groom do not have time in preparing these things. For that, a place that can facilitate the needs of the bride and groom is needed to make it easier for them in preparing their needs. The interior design of this Wedding Centre meets the main needs in preparation before the wedding such as boutique, salon, photo studio, event organizer room, and cafeteria. These facilities can be used by the prospective bride and groom and also general visitors. The theme of this design is the "gallery" that displays a simple impression by applying elegant colors. The amount of furniture used in this design is not that many so that the appearance of the wedding dress on display will be more prominent.